Comparison of the efficiencies of attached- versus suspended-growth SBR systems in the treatment of recycled paper mill wastewater. (1st November 2015) - Muhamad, Mohd Hafizuddin; Sheikh Abdullah, Siti Rozaimah; Abu Hasan, Hassimi; Abd. Rahim, Reehan Adnee
Abstract: The complexity of residual toxic organics from biologically treated effluents of pulp and paper mills is a serious concern. To date, it has been difficult to choose the best treatment technique because each of the available options has advantages and drawbacks. In this study, two different treatment techniques using laboratory-scale aerobic sequencing batch reactors (SBRs) were tested with the same real recycled paper mill effluent to evaluate their treatment efficiencies. Two attached-growth SBRs using granular activated carbon (GAC) with and without additional biomass and a suspended-growth SBR were used in the treatment of real recycled paper mill effluent at a chemical oxygen demand (COD) level in the range of 800–1300 mg/L, a fixed hydraulic retention time of 24 h and a COD:N:P ratio of approximately 100:5:1. The efficiency of this biological treatment process was studied over a 300-day period. The six most important wastewater quality parameters, namely, chemical oxygen demand (COD), turbidity, ammonia (expressed as NH3 –N), phosphorus (expressed as PO4 3 –P), colour, and suspended solids (SS), were measured to compare the different treatment techniques. It was determined that these processes were able to almost completely and simultaneously eliminate COD (99%) and turbidity (99%); the removals of NH3 –N (90–100%), PO4 3 –P (66–78%), colour (63–91%), and SS (97–99%) were also sufficient. The overall performance results confirmed that an attached-growth SBR system using additional biomass on GAC is a promising configuration for wastewater treatment in terms of performance efficiency and process stability under fluctuations of organic load. Hence, this hybrid system is recommended for the treatment of pulp and paper mill effluents. Graphical abstract: Highlights: The attached- (AG) and suspended-growth (SG) SBR systems were compared. All treatment processes were tested with real recycled paper mill wastewater. The treatment study was conducted over a 300-day period. The AG-SBR using additional biomass on GAC showed a stable removal of COD (95%).